A power efficient gain enhancing technique for current mirror operational transconductance amplifiers. Issue 2 (February 2015) - Ali, Shafqat
Abstract In this paper, a power efficient voltage gain enhancing technique is described. This technique is suitable for the amplifiers which use current starving method for gain enhancement (explained in the text). The proposed technique makes use of the current which conventionally goes to ground, through a parallel path. In this paper, the new technique is demonstrated for current mirror type of operational transconductance amplifier (OTA). Simulation results show that gain improves by a factor ~2, while consuming the same power as conventional OTA. The added advantage of this technique is that it does not affect the voltage swing while increasing the gain. Compared to the conventional current starving technique, the proposed technique also improves the noise performance and settling speed of the amplifier. The results are compared with the conventional technique, in terms of gain, settling and noise performance. A comparison of FoM (MHz.pF/mA), with other amplifiers, is given at the end as well.